Cosmologies of the Anthropocene - Vetlesen, Arne Johan, 1960- author.
1 online resource.
Keywords: This book engages with the classic philosophical question of mind and matter, seeking to show its altered meaning and acuteness in the era of the Anthropocene. Arguing that matter, and, more broadly, the natural world, has been misconceived since Descartes, it explores the devastating impact that this has had in practice in the West. As such, alternatives are needed, whether philosophical ones such as those offered by figures such as Whitehead and Nagel, or posthumanist ones such as those developed by Barad and Latour. Drawing on recent anthropological work ignored by philosophers and sociologists alike, the author considers a radical alternative cosmology: animism understood as panpsychism in practice. This understanding of mind and matter, of culture and nature, is then turned against present-day posthumanist critiques of what the Anthropocene amounts to, showing them up as philosophically misguided, politically mute, and ethically wanting. A ground-breaking reconceptualization of the natural world and our treatment of it, Cosmologies of the Anthropocene will appeal to scholars of sociology, social theory, philosophy and anthropology with interests in our understanding of and relationship with nature.